2013
DOI: 10.1089/end.2012.0262
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Learning Curve of Experienced Laparoscopic Surgeons in Robot-Assisted Radical Prostatectomy

Abstract: The initial results of the outcome of RALP are at least at par with those of LRP and with those of previously published RALP series. This suggests the lack of a steep learning curve for experienced laparoscopic surgeons in performing RALP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 29 publications
2
19
0
4
Order By: Relevance
“…The anatomical complexities as described above show the importance of the 3-step apical dissection procedure: (1) santorini plexus dissection, (2) dissection between the EUS striated and smooth muscle components and (3) dissection of the inner urethral muscular layer [7] ; this is summarized in figure 5 . With LRP, apical dissection is more difficult to be performed because of the lack of wristed instruments and the lack of space at the apex of the prostate, which lead to the possibility of greater traction on nerves [16] . This is supported by recent evidence of a shorter learning curve for apical PSM rates in RARP in comparison to LRP, with the robotic modality thought to improve a surgeons' apical dissection [2] .…”
Section: Discussionmentioning
confidence: 99%
“…The anatomical complexities as described above show the importance of the 3-step apical dissection procedure: (1) santorini plexus dissection, (2) dissection between the EUS striated and smooth muscle components and (3) dissection of the inner urethral muscular layer [7] ; this is summarized in figure 5 . With LRP, apical dissection is more difficult to be performed because of the lack of wristed instruments and the lack of space at the apex of the prostate, which lead to the possibility of greater traction on nerves [16] . This is supported by recent evidence of a shorter learning curve for apical PSM rates in RARP in comparison to LRP, with the robotic modality thought to improve a surgeons' apical dissection [2] .…”
Section: Discussionmentioning
confidence: 99%
“…All other parameters (catheterization time, positive surgical margins and continence rates) were reported to be similar. The authors commented that a good laparoscopy experience quells a steep learning curve of robotic surgery (15). In another quite similar study, the first 60 RRP and the last 60 LRP results of 3 surgeons with over 200 LRP experience were compared and it was reported that surgery time, blood loss volume and surgical margin positivity were significantly higher in patients who underwent robotic prostatectomy (153 mins-236 mins, 202 ml-244 ml and 12.5-31.6%, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Apesar da redução nas taxas no momento 4, visualizada no gráfico 9, não foi demostrada diferença estatística entre o percentual de PSA detectável nos quatro grupos aos 6 meses (p= 0,2902) ou 1 ano (p= 0,3694) após a cirurgia. Atualmente, há um número limitado de programas de fellowship em PRL nos países em desenvolvimento, nos quais a maioria dos preceptores foram treinados inicialmente na Europa ou Estados Unidos, onde a técnica robótica é, hoje, responsável por cerca de 95% dos tratamentos minimamente invasivos para câncer de prostata [32].…”
Section: 6-análise Dos Níveis De Psaunclassified
“…Stolzenburg demostrou que a experiência em PRL praticamente anula a curva de aprendizado em PRLAR, pois os passos técnicos são similares e a ausência de feedback tátil do sistema robótico pode ser compensado pela familiaridade visual adquirida na PRL [32].…”
Section: 6-análise Dos Níveis De Psaunclassified
See 1 more Smart Citation